CRITICAL DISCOURSE ANALYSIS OF SINGLE TUITON FEE INCREASE IN MASS MEDIA - Njue Steeven Tarigan; Rahmad Ardiansyah, Albert Hezekiah Sanolo Zebua, Rafi Ryandieka Adinulhaq (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
News about student demonstrations regarding the impact of the increase in single tuition fees (UKT) after National Education Day has been widely reported, including in the mass media Tempo.co, Kalderanews.com, and Radarbanyumas.disway.id. It is certain that the perception and discourse of news from each mass media is different. Using Teun Van Dijk's Critical Discourse Analysis (CDA) method, this research aims to examine the discourse, social cognition and social context in mass media reports regarding the increase in Single Tuition Fees (UKT) in several State Universities after National Education Day on May 2 2024 . This research uses a qualitative method by collecting data through observing the three news stories and analyzing them using the Van Dijk CDA framework which includes macro structure, superstructure and microstructure (Semantics & Syntax). This study explains that the three news stories have the same topic, but the news is presented with different sub-themes and styles. These findings highlight that news articles depict students in a protest role, while universities and the Ministry as the guilty parties, indicating a lack of concern for students. This analysis highlights the role of the media in shaping public perceptions of the phenomenon.